Juridical Review of the Increase of VAT to 12 Percent in Law Number 7 of 2021 on the Harmonization of Tax Regulations - Rizky Alifi; Elvira Fitriyani Pakpahan; Kartina Pakpahan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This research discusses the Harmonization of the 12 Percent Value Added Tax (VAT) Increase in Law Number 7 of 2021 concerning the Harmonization of Tax Regulations. The study focuses on three main issues: (1) how the harmonization of the 12 percent VAT increase is regulated under Law Number 7 of 2021, (2) how the legal protection for society is ensured within the principle of justice regarding the VAT increase, and (3) how local governments contribute to the implementation of the 12 percent VAT increase. The research method used is a normative legal approach by employing primary legal materials such as legislation, secondary legal materials including books, journals, and expert opinions, as well as tertiary legal materials. The analysis is carried out qualitatively, emphasizing principles, theories, and the practice of tax law in Indonesia. The results show that, first, the harmonization of the 12 percent VAT increase is intended to strengthen state revenue post-COVID-19 pandemic through regulatory consolidation, implemented in derivative regulations such as Government Regulations and Minister of Finance Regulations to ensure legal certainty and consistent implementation. Second, legal protection for society within the principle of justice is realized through the exemption of basic necessities, facilities for micro, small, and medium enterprises (MSMEs), subsidies and social assistance for vulnerable groups, as well as objection and appeal mechanisms within the tax court system. Third, the efforts of local governments are manifested in public socialization and education, cooperation with the Directorate General of Taxes, and the provision of regional social protection programs to mitigate the negative impact on people’s purchasing power. The study concludes that the harmonization of the 12 percent VAT increase can be effectively implemented if it is accompanied by strong legal protection and responsive efforts from local governments. Therefore, both central and local governments are expected to strengthen synergy, broaden legal protection, and enhance socialization to ensure that the VAT policy aligns with the principle of social justice for all Indonesian people.